INKONSISTENSI EJAAN BAKU AKIBAT PENAMBAHAN BUNYI VOKAL /ə/ DALAM KAMUS BESAR BAHASA INDONESIA - Brigitta Sita Oentari (EPIGRAM (e-journal), 2023)
As a reference source, dictionaries play a major role in providing linguistic information to the speech community as accurately as possible. One of which is the standard form. The use of the standard words required for formal situations and official communication demands the establishment of standard and consistent rules. This study aims to identify and describe the standard spelling inconsistencies caused by anaptyxis, or the addition of the vowel sound /ə/ in KBBI or the Fifth Edition of the Big Indonesian Dictionary (2018). This mixed research refers to the application of dictionaries as a result of codification (Kaplan & Baldauf, 1997) and the use of existing dictionaries as a data source for lexicography (Lauder, 2010). The note-taking method is used to analyze a research data sample of 40 standard and non-standard words in KBBI. The results showed that there are two types of standard spellings based on the presence or absence of the vowel /ə/ anaptyxis between the consonant clusters. The first type is the standard form, which contains anaptyxis, and the second type is the standard form, which does not contain anaptyxis. The first type dominates the data by 57.5% and shows that the Indonesian standard spelling is dominated by forms that insert the vowel /ə/ between the consonant clusters. The second type, whose standard form does not contain anaptaxis, can be seen in the nine categories of consonant clusters, with /tr/, /st/, and /sp/ as the most dominant consonant clusters. These findings indicate that there is a discrepancy in the rules of standard form when standardization is truly needed to direct speech community to be able to use the language according to the rules.